Flexible fireproof cable with halogen-free ultra-thin mica tape composite

CN121460285BActive Publication Date: 2026-10-20GUANGZHOU LINGNAN CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511931958.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-19
Publication Date
2026-10-20
Estimated Expiration
2045-12-19

AI Technical Summary

Technical Problem

含卤防火电缆燃烧时会释放氯化氢、溴化氢等有毒气体,伴随大量浓烟,不仅污染环境,还会严重阻碍人员疏散与救援工作,引发二次灾害

Benefits of technology

[0018]本发明提供了一种邻腈无卤超薄云母带复合的柔性防火电缆,包含有导体、邻腈无卤超薄云母带复合层。其中所述复合层包含有由单体A、B、C聚合形成的邻腈无卤聚合物与超薄云母片,多种防火机制协同作用,可达到高效阻燃、耐高温、绝缘、疏水及高柔性的技术效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121460285B_ABST
    Figure CN121460285B_ABST
Patent Text Reader

Abstract

The application discloses a kind of adjacent nitrile halogen-free ultra-thin mica tape composite flexible fireproof cable, belong to cable technical field.The cable includes conductor and adjacent nitrile halogen-free ultra-thin mica tape composite layer from inside to outside successively.The composite layer includes 30-40 weight parts mica sheet and 100 weight parts adjacent nitrile halogen-free polymer, and the polymer is formed by the copolymerization of specific molar ratio of monomer A (containing phosphorus structure), monomer B (1,7-divinyl-octamethyltetrasiloxane) and monomer C (containing adjacent nitrile group).The application is by "nitrogen-phosphorus-silicon" synergistic flame-retardant mechanism, combined with the high-temperature stability of ultra-thin mica sheet, so that the cable has excellent fireproof performance, halogen-free environmental protection, high flexibility, good hydrophobicity and higher mechanical strength and residual carbon rate, and is suitable for high-rise building, rail transit and other occasions with strict requirements on fireproofing and flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable technology, specifically to a flexible fireproof cable made of nitrile-free halogen-free ultrathin mica tape composite. Background Technology

[0002] Traditional fire-resistant cables typically use mica tape of standard thickness as the fire-resistant base material, combined with halogenated flame retardants or ordinary halogen-free resins to achieve fire resistance, but this approach has significant drawbacks. Halogenated fire-resistant cables release toxic gases such as hydrogen chloride and hydrogen bromide when burning, accompanied by large amounts of dense smoke. This not only pollutes the environment but also severely hinders personnel evacuation and rescue efforts, potentially causing secondary disasters. While existing halogen-free fire-resistant cables avoid the release of toxic gases, they often use epoxy or phenolic resins as binders, which lack sufficient high-temperature resistance. They are prone to decomposition and carbonization in flames exceeding 950°C, and their fire resistance time is typically only 90-120 minutes, far from meeting the stringent requirements of high-rise buildings and rail transit systems for long-term fire resistance exceeding 180 minutes.

[0003] In terms of structure and flexibility, traditional mica tape is typically 0.15-0.20mm thick. To ensure fire resistance, multiple layers of wrapping are required, resulting in a 30%-50% increase in the overall cable diameter and a significant increase in weight. This not only increases installation difficulty but also makes it unsuitable for wiring in confined spaces. Furthermore, traditional cables have poor flexibility, with bending radii generally exceeding 10D (where D is the cable diameter). In scenarios requiring frequent bending, such as building corners and equipment connections, insulation cracking and fireproofing peeling are highly likely, severely impacting safety and lifespan.

[0004] There are also shortcomings in terms of material compatibility and performance balance. Traditional mica tape has poor compatibility with resin, and delamination and detachment are prone to occur during long-term use or in hot and cold cycling environments, directly leading to the failure of the fireproof layer. In addition, existing halogen-free fireproof cables cannot balance mechanical properties and fireproof performance. Some products sacrifice tensile strength and elongation at break to improve fire resistance, making them prone to damage during installation and use; while simply pursuing mechanical strength will lead to a decrease in fire resistance, making it difficult to achieve optimal overall performance.

[0005] Existing technical solutions have not yet effectively solved the above problems. For example, although some flexible fire-resistant cables claim to have insulation and fire-resistant properties, their synergistic effect of flexibility and long-term fire resistance has not been fully verified. Some solutions that use fluorine-containing materials such as PVDF as sheaths may still produce toxic and corrosive gases at high temperatures. Multi-layer composite structure designs have also failed to overcome the limitations of thickness and weight. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a flexible fire-resistant cable made of nitrile-free halogen-free ultra-thin mica tape composite, achieving the following objectives: 1. Reducing cable thickness and weight, and improving flexibility; 2. Achieving halogen-free environmental protection, with no toxic gases or dense smoke generated during combustion; 3. Improving fire resistance stability, meeting the requirement of long-term fire resistance of more than 180 minutes; 4. Balancing excellent mechanical properties and aging resistance.

[0007] This invention provides a flexible fire-resistant cable with an o-nitrile halogen-free ultrathin mica tape composite, comprising, from the inside out, a conductor and an o-nitrile halogen-free ultrathin mica tape composite layer. The o-nitrile halogen-free ultrathin mica tape composite layer of the cable may also be covered with a protective sheath.

[0008] The o-acrylonitrile-free halogen-free ultrathin mica tape comprises 30-40 parts (by weight) of 30-80 μm thick ultrathin mica sheets and 100 parts (by weight) of o-acrylonitrile-free polymer.

[0009] The o-nitrile halogen-free polymer is polymerized from monomers A, B, and C, with the molar ratio of monomers A, B, and C being (25-35):(80-90):(30-40).

[0010] The monomer A has the structure of Formula 1: Formula 1.

[0011] The monomer B is 1,7-divinyl-octamethyltetrasiloxane, with the structural formula shown below: .

[0012] The monomer C has the structure of Formula 2: Formula 2.

[0013] The monomer A is prepared by reacting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) with oct-4-ene-1,8-dialdehyde at 60-100℃ for 10-24h; the molar ratio of DOPO to oct-4-ene-1,8-dialdehyde is (2.05-2.1):1.

[0014] The monomer C is prepared as follows: the carboxyl group of acrylic acid is activated by EDC and NHS, and then reacted with compound p-NH2-Bn-DTPA (S-2-(4-aminobenzyl)-diethylenetriaminepentaacetic acid) to obtain intermediate product I; the carboxyl group of intermediate product I is activated by EDC and NHS, and then reacted with 4-aminophthalonitrile to prepare the product.

[0015] The preparation method of the o-nitrile halogen-free polymer is as follows: Monomers A, B, and C were added to a THF solution in the specified amounts, followed by 0.3%-1% AIBN catalyst (based on the total mass of monomers A, B, and C). The reaction was carried out under nitrogen protection at 60-100℃ for 6-12 hours. The molar ratio of monomers A, B, and C was (25-35):(80-90):(30-40).

[0016] The preparation method of the flexible cable with o-nitrile halogen-free ultrathin mica tape composite is as follows: 30-40 parts (by weight) of ultrathin mica sheets and 100 parts (by weight) of o-nitrile halogen-free polymer are mixed evenly under a nitrogen atmosphere at 260-280°C, and then hot-extruded and wrapped around a conductor (core) to prepare a flexible cable with an outer layer of o-nitrile halogen-free ultrathin mica tape composite layer. The thickness of the o-nitrile halogen-free ultrathin mica tape composite layer is between 1 mm and 5 mm.

[0017] Beneficial effects

[0018] This invention provides a flexible fire-resistant cable with o-nitrile halogen-free ultrathin mica tape composite, comprising a conductor and an o-nitrile halogen-free ultrathin mica tape composite layer. The composite layer comprises an o-nitrile halogen-free polymer formed by the polymerization of monomers A, B, and C, and ultrathin mica sheets. Multiple fire-retardant mechanisms work synergistically to achieve high-efficiency flame retardancy, high-temperature resistance, insulation, hydrophobicity, and high flexibility.

[0019] Monomer A is rich in phosphorus. After high-temperature decomposition, it releases phosphorus-containing free radicals such as PO· and HPO·, which quickly capture H· and ·OH active free radicals in the flame, interrupting the combustion chain reaction. Furthermore, the phosphoric acid and polyphosphoric acid produced during decomposition catalyze the dehydration and carbonization of the polymer surface, forming a carbon layer that can isolate heat and oxygen. Secondly, monomer A has a certain degree of hydrophobicity, which can be combined with monomer B to enhance the hydrophobicity of the o-nitrile halogen-free ultrathin mica tape composite layer.

[0020] Monomer B is 1,7-divinyl-octamethyltetrasiloxane, which, after polymerization with monomers A and C, forms an interpenetrating network skeleton rich in siloxane chains (-Si-O-Si-). This not only enhances the mechanical strength, flexibility, and waterproof performance of the composite layer, but also possesses excellent fire-retardant properties based on the unique chemical structure and combustion behavior of siloxanes. The core mechanisms include two points: 1. Thermal stability of the high bond energy skeleton. The Si-O covalent bond energy of the siloxane backbone is much higher than that of carbon-carbon and carbon-oxygen bonds, giving the polymer extremely strong thermal stability: the decomposition temperature is as high as 350-400℃ (far higher than the 200-300℃ of traditional organic polymers such as polyethylene and epoxy resin); at high temperatures (such as in fire environments), the backbone is less prone to breakage, avoiding the generation of a large number of flammable small molecules (such as methane and olefins), thus inhibiting the initiation of the combustion reaction from the source. 2. Physical barrier effect of combustion to char (key mechanism). When the polymer burns, the siloxane backbone undergoes controlled degradation, forming a dense SiO2 / C composite char layer (commonly known as a "ceramicized char layer").

[0021] Monomer C contains multiple o-nitrile benzene groups, which can polymerize at high temperatures to form a dense carbon layer, providing highly efficient fire resistance. It is also rich in nitrogen, allowing it to work in conjunction with monomer A to achieve a synergistic fire-retardant effect of nitrogen and phosphorus. Furthermore, monomer C is rich in nitrogen and oxygen atoms or groups, enabling strong intermolecular interactions with mica sheets, such as hydrogen bonds. This effectively enhances the coating effect of the o-nitrile halogen-free polymer on the mica sheets, thereby ensuring the mechanical strength of the o-nitrile halogen-free ultrathin mica tape composite layer.

[0022] The flexible fireproof cable of the present invention, which is a composite of nitrile halogen-free ultrathin mica tape, can achieve the technical effects of high flame retardancy, high temperature resistance, insulation, hydrophobicity and high flexibility through the interaction of nitrile halogen-free polymer formed by the polymerization of monomers A, B and C in the composite layer and ultrathin mica sheets. This is achieved through the interaction of char formation and silica, nitrile cross-linking char formation and mica high temperature resistance and fire resistance. Attached Figure Description

[0023] Figure 1 This is a flowchart of the synthesis process for monomer A.

[0024] Figure 2 This is a flowchart of the synthesis process for monomer C.

[0025] Figure 3 This is a flowchart of the synthesis of halogen-free nitrile polymers.

[0026] Figure 4 The image shows the infrared spectrum of monomer C. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] The raw materials used in the examples and comparative examples are described below: Oct-4-ene-1,8-dialdehyde: purchased from Henan Weitixi Chemical Technology Co., Ltd., CAS: 51097-60-0.

[0029] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO): Zhengzhou Alpha Chemical Co., Ltd.

[0030] EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide): purchased from Guangzhou Baide Biotechnology Co., Ltd.

[0031] NHS (N-hydroxysuccinimide): Purchased from Hubei Xinghengkang Chemical Technology Co., Ltd.

[0032] Azobisisobutyronitrile (AIBN): Shanghai Aladdin Biochemical Technology Co., Ltd.

[0033] p-NH2-Bn-DTPA (S-2-(4-aminobenzyl)-diethylenetriaminepentaacetic acid): purchased from Xi'an Kangfuno Biotechnology Co., Ltd., CAS: 102650-29-3.

[0034] 4-Aminophthalonitrile: Purchased from Zhengzhou Huiju Chemical Co., Ltd.

[0035] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the components and raw materials used in each parallel experiment or comparative experiment are the same, and the experimental methods used are all carried out under the same conditions.

[0036] Preparation of monomer A (self-made): Under a nitrogen atmosphere, 2.05 mol DOPO and 1 mol oct-4-en-1,8-dialdehyde were dissolved in 5 L xylene, the pH was adjusted to 8 with triethylamine, and the reaction was carried out at 75 °C for 24 h. After purification and drying, the product was obtained.

[0037] Preparation of monomer C (self-made): 1.1 mol of acrylic acid was dissolved in anhydrous DMF, and the carboxyl group was activated by stirring at 200 rpm for 2 h with 1.15 mol EDC and 1.2 mol NHS in sequence. 1 mol of compound p-NH2-Bn-DTPA (S-2-(4-aminobenzyl)-diethylenetriaminepentaacetic acid) in DMF solution was added dropwise to the above activation solution and the reaction was stirred at 200 rpm for 4 h. Intermediate product I was obtained by preparative liquid chromatography purification.

[0038] Intermediate product I (0.96 mol) was dissolved in DMF, and the carboxyl group was activated by stirring with 1.1 mol EDC and 1.2 mol NHS at 200 rpm for 2 h. Then, 5.5 mol of 4-aminophthalonitrile DMF solution was added dropwise, and the reaction was stirred at 200 rpm for 6 h. The mixture was purified by preparative liquid chromatography to obtain monomer C (see...). Figure 4 In the infrared spectrum of monomer C, the NH stretching vibration of the amide bond appears at 3292 cm⁻¹; the carbonyl C=O stretching peak is located at 1670 cm⁻¹; the cyano CN characteristic peak is located at 2232 cm⁻¹; and the olefinic hydrogen=CH stretching vibration peak is located at 3082 cm⁻¹.

[0039] Example 1

[0040] A method for preparing a flexible cable with o-nitrile halogen-free ultrathin mica tape composite is as follows: 36 parts (by weight) of 50 μm thick ultrathin mica sheets and 100 parts (by weight) of o-nitrile halogen-free polymer were mixed uniformly under a nitrogen atmosphere at 265°C, and then hot-extruded and wrapped around a conductor (battery cell: 50mm copper cell). 2 A cable is prepared with an outer layer of 1mm thick acrylonitrile-free halogen-free ultrathin mica tape composite layer.

[0041] The preparation method of the o-nitrile halogen-free polymer is as follows: Monomers A, B, and C were added to a THF solution in the specified amounts, followed by 0.6% (by mass) of AIBN catalyst (based on the total mass of monomers A, B, and C). The reaction was carried out under nitrogen protection at 70°C for 10 hours. The molar ratio of monomers A, B, and C was 29:86:35.

[0042] Examples 2-5 The preparation methods of Examples 2-5 are the same as those of Example 1, except that the amount of mica sheets and the molar ratio of each monomer used in the preparation of the o-nitrile halogen-free polymer are adjusted.

[0043] Comparative Example 1 The preparation method of Comparative Example 1 is the same as that of Example 1, except that the amount of monomer A is reduced when preparing the o-nitrile halogen-free polymer.

[0044] Comparative Example 2 The preparation method of Comparative Example 2 is the same as that of Example 1, except that the amount of monomer B is reduced when preparing the o-nitrile halogen-free polymer.

[0045] Comparative Example 3 The preparation method of Comparative Example 3 is the same as that of Example 1, except that the amount of monomer C is reduced when preparing the o-nitrile halogen-free polymer.

[0046] Comparative Example 4 The preparation method of Comparative Example 4 is the same as that of Example 1, except that the amount of mica sheets used is reduced.

[0047] Comparative Example 5 The preparation method of Comparative Example 5 is the same as that of Example 1, except that the amount of mica sheets used is increased.

[0048] Comparative Example 6 The preparation method of Comparative Example 6 is the same as that of Example 1, except that the thickness of the o-nitrile halogen-free ultrathin mica tape composite layer is adjusted from 1 mm to 0.6 mm.

[0049] Table 1 Comparison of preparation methods for the examples and comparative examples

[0050] Performance verification tests: The performance of the cables, o-nitrile halogen-free polymers, or o-nitrile halogen-free ultrathin mica tape composite layers (materials) prepared in the examples and comparative examples were verified.

[0051] 1. Tensile test Sample preparation: dumbbell-shaped sample (GB / T1040.1-2006, Type 1A), test object: cyano-acid halogen-free ultrathin mica tape composite material (specifically refers to the material prepared by mixing cyano-acid halogen-free polymer with mica sheets).

[0052] Test method: Tensile strength (MPa) and elongation at break (%) were determined using a tensile testing machine at a tensile speed of 50 mm / min.

[0053] 2. Fire resistance GB / T19216.21-2003 Bundle burning tester, smoke density tester, fire resistance time (min), HCl release (mg / g).

[0054] 3. Flexibility IEC60228-2004 Flexibility performance - Minimum bending radius (D, cable diameter) determined by a bending tester.

[0055] 4. Hydrophobicity test Sample preparation: Each sample was processed into a smooth sheet-like sample of 50mm×50mm×2mm. The surface was wiped with alcohol and then dried (test object: cyanocyanate halogen-free ultrathin mica tape composite layer).

[0056] Test method: According to GB / T30693-2014, use a contact angle measuring instrument, add 5μL of deionized water to the sample surface at 25℃ and 50% relative humidity, and record the static contact angle.

[0057] 5. Residual carbon content The thermal stability of the o-acrylonitrile-free polymer was tested using a thermogravimetric analyzer (TGA, TAQ50) and in accordance with standard GB / T2951.41-2008. Approximately 50 mg of the o-acrylonitrile-free polymer was placed in a crucible and heated from room temperature to 800 °C at a rate of 10 °C / min under a nitrogen atmosphere, with a nitrogen flow rate of 50 mL / min.

[0058] Table 2 Performance Test Results Record Sheet

[0059] According to the data in Table 2, 1) the tensile strength of Examples 1-5 can reach 23.3 MPa-26.5 MPa. Compared with Example 1, the amount of monomer B (1,7-divinyl-octamethyltetrasiloxane) in Comparative Example 2 is reduced. Monomer B can play a cross-linking role in the o-nitrile halogen-free polymer. Obviously, the reduction in the amount of monomer B leads to a significant decrease in the tensile strength of Comparative Example 2. In Comparative Examples 1 and 3, the amount of monomer A or monomer C is reduced, resulting in an increase in the relative amount of monomer B. This also explains the increase in tensile strength of Comparative Examples 1 and 3 compared to Example 1. Compared with Example 1, Comparative Example 5 increases the amount of mica sheet. As a fire-retardant material doped in the o-nitrile halogen-free ultrathin mica tape composite layer, although the mica sheet can form intermolecular forces such as hydrogen bonds with the o-nitrile halogen-free polymer, it is still not as strong as the intramolecular covalent bond strength of the o-nitrile halogen-free polymer. Therefore, it leads to a decrease in the tensile strength of the o-nitrile halogen-free ultrathin mica tape composite layer (material) of Comparative Example 5. 2) The fire resistance times of Examples 1-5 ranged from 230 min to 265 min, all exceeding the 180 min fire resistance requirement. However, compared to Example 1, Comparative Examples 1-6 showed a significant decrease in fire resistance performance. This indicates that the ratio of monomers A, B, and C, as well as the ratio of the o-acrylonitrile-free polymer to mica flakes, are important factors affecting the fire resistance time. Comparative Examples 1-3 demonstrate that monomers A, B, and C can form a "nitrogen, phosphorus, and silicon" fire retardant system, and that monomers A (containing phosphorus), B (containing silicon), and C (containing nitrogen) can achieve a synergistic and efficient fire retardant effect through the specific ratios shown in Examples 1-5. Comparative Examples 4 and 5 reduced and increased the amount of mica flakes, respectively. Mica flakes can effectively resist high temperatures; a small amount is insufficient for temperature resistance, while a large amount results in a relatively small amount of o-acrylonitrile-free polymer, making it difficult to effectively encapsulate the mica flakes and form a continuous char layer, thus weakening the fire retardant effect. However, in Comparative Example 6, the thickness of the 0.6mm thick halogen-free ultrathin mica tape composite layer was insufficient, resulting in a significant reduction in fire resistance. 3) Based on the minimum bending radius, the cables prepared in Examples 1-5 exhibit good flexibility, with a minimum bending radius of 3.6D-4.1D, which is beneficial for cable construction. However, the relatively high amount of monomer B in Comparative Examples 1 and 3 leads to a higher degree of crosslinking, resulting in a larger bending radius and a lower elongation at break. The relatively low amount of monomer B in Comparative Example 2 leads to a lower degree of crosslinking, resulting in a smaller bending radius, but a significant reduction in tensile strength. Comparative Examples 4 and 5 show that the doping amount of mica sheets has a negative correlation with the flexibility of the cable. 4) The water contact angle of Examples 1-5 is between 105.7° and 110.2°, indicating that the cables prepared in Examples 1-5 have good hydrophobicity. Compared to Example 1, the water contact angle of Comparative Example 2 was reduced to 94.5°, indicating that monomer B plays a key role in regulating hydrophobic properties; compared to Comparative Example 2, Comparative Example 1 shows that monomer A also possesses hydrophobic properties.5) The char residue rates of Examples 1-5 ranged from 68.8% to 72.1%, indicating that the o-nitrile halogen-free polymer can form a dense char layer at high temperatures, which can block the transfer of flame heat to the interior of the material and isolate oxygen from contact with the combustible substrate, thus inhibiting the continuation of combustion from the source. Compared with Example 1, Comparative Examples 1-3 show that monomers A, B, and C can effectively synergistically improve the char formation rate and enhance fire resistance.

[0060] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A flexible fire-resistant cable with halogen-free ultra-thin mica tape composite, characterized in that, From the inside out, it comprises a conductor and an o-nitrile halogen-free ultrathin mica tape composite layer; by weight, the o-nitrile halogen-free ultrathin mica tape contains 30-40 parts of mica sheets and 100 parts of o-nitrile halogen-free polymer; the o-nitrile halogen-free polymer is polymerized from monomers A, B, and C, wherein monomer A has the structure of Formula 1: Formula 1; the monomer B is 1,7-divinyl-octamethyltetrasiloxane; the monomer C has the structure of Formula 2: Formula 2.

2. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that: The molar ratio of monomer A, monomer B, and monomer C is (25-35):(80-90):(30-40).

3. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that: The thickness of the mica sheet is 30~80μm.

4. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that, The thickness of the halogen-free ultrathin mica tape composite layer is between 1mm and 5mm.

5. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that, The monomer A is prepared by reacting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with oct-4-ene-1,8-dialdehyde at 60-100℃ for 10-24h.

6. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 5, characterized in that, The molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to oct-4-ene-1,8-dialdehyde is (2.05-2.1):

1.

7. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that, The monomer C is prepared as follows: the carboxyl group of acrylic acid is activated by EDC and NHS, and then reacted with compound S-2-(4-aminobenzyl)-diethylenetriaminepentaacetic acid to obtain intermediate product I; the carboxyl group of intermediate product I is activated by EDC and NHS, and then reacted with 4-aminophthalonitrile to prepare the product.

8. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that, The preparation method of the o-nitrile halogen-free polymer is as follows: Add monomers A, B, and C to a THF solution in the specified amounts, and add 0.3%-1% of AIBN catalyst based on the total mass of monomers A, B, and C. Under nitrogen protection, react at 60-100℃ for 6-12 hours. The molar ratio of monomers A, B, and C is (25-35):(80-90):(30-40).

9. The flexible fire-resistant cable with halogen-free ultra-thin mica tape composite as described in claim 1, characterized in that, The outer layer of the nitrile halogen-free ultrathin mica tape composite layer is also covered with a protective sleeve.

10. The method for preparing the flexible fire-resistant cable with o-nitrile halogen-free ultrathin mica tape composite according to any one of claims 1-9, characterized in that: 30-40 parts by weight of ultrathin mica sheet and 100 parts by weight of o-nitrile halogen-free polymer are mixed evenly under nitrogen atmosphere at 260-280°C, and then hot-extruded and wrapped around a conductor to prepare a flexible cable with an outer layer of o-nitrile halogen-free ultrathin mica tape composite layer. The thickness of the o-nitrile halogen-free ultrathin mica tape composite layer is between 1 mm and 5 mm.

Citation Information

Patent Citations

  • High-temperature-resistant and high-flame-retardant cable

    CN116218092A

  • Thermoplastic rubber material for high-voltage cable of new energy automobile and preparation method of thermoplastic rubber material

    CN118256041A